Best practices in early literacy instruction - Barone, Diane M., editor; Mallette, Marla H., editor (New York : Guilford Press, 2013)
"Bringing together prominent scholars, this book shows how 21st-century research and theory can inform everyday instructional practices in early childhood classrooms (PreK-3). Coverage includes foundational topics such as alphabet learning, phonological awareness, oral language development, and learning to write, as well as cutting-edge topics such as digital literacy, informational texts, and response to intervention. Every chapter features guiding questions; an overview of ideas and findings on the topic at hand; specific suggestions for improving instruction, assessment, and/or the classroom environment; and an engrossing example of the practices in action"--provided by publisher